2019
DOI: 10.1002/slct.201803583
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of MgTiO3 Nanoparticles for Photocatalytic Applications

Abstract: Magnesium titanate (MgTiO3) has been successfully synthesized via the sonochemical method by using TiO2 (P25) and Magnesium nitrate (MgNO3)2.6H2O as precursors without any additional phases such as MgTi2O5 and Mg2TiO4. The synthesized nanoparticles were well characterized by optical methods using UV‐Vis diffuse reflectance spectroscopy (DRS) and Photoluminescence spectroscopy (PL). The morphology of MgTiO3 nanoparticles is irregular in shape with serious agglomerations were confirmed through SEM analysis. XRD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 50 publications
1
17
0
Order By: Relevance
“…Moreover, the band gaps of the composites ( Figure S3) also followed direct allowed transitions as well as for pristine WO 3 .…”
Section: Uv-vis Studiesmentioning
confidence: 68%
See 4 more Smart Citations
“…Moreover, the band gaps of the composites ( Figure S3) also followed direct allowed transitions as well as for pristine WO 3 .…”
Section: Uv-vis Studiesmentioning
confidence: 68%
“…The highest band gap of 4.92 eV was observed for pristine WO 3 . The band gaps are summarized by table 1 and from Figure 9 it can be observed that the band gap of the composite degreased to 2.27 eV.…”
Section: Uv-vis Studiesmentioning
confidence: 97%
See 3 more Smart Citations